Investigating the use of an online classroom in understanding the learning process of KUiTTHO students - Foo, Jyy Wei (2002)
The aim of this research is to investigate how KUiTTHO students use an online classroom for the purpose of learning technical subjects, to identify the topics discussed by the KUiTTHO students in an online classroom, to investigate their behavior act during and after using the online classroom over a period of time and to evaluate the influence of online classroom toward standard interaction and learning. This research adopted a combination of qualitative and quantitative research. The participants of this research were the students of Electrical Department at KUiTTHO. These students were the ones taking electrical course (technical subject) that was Circuit Theory during their study at KUiTTHO. The researcher used four methods in data collection. There are interview, observation, content analysis and questionnaires. Nicenet is used in collecting the data in this research. At the end of this research, the finding shows that the participants showed their interest in online classroom. Most of them agree that Nicenet should be applied into the process of teaching and learning the technical subject in institution of higher education in Malaysia.